Prospects of FEV6 using as alternative indicator of respiratory function assessment - Myronenko, O. V.; Fesenko, O. V.; Dmytrychenko, V. V.; Zhulay, K. V. (Zaporozhye Medical Journal, 2017)
The aim of the study was to establish a correlation between the changes of external respiratory function leading indicators in patients with COPD and the presence of a positive response to the bronchodilator over an extended period of observation and the value of the FEV6 index in assessment of bronchial obstruction reversibility. Materials and methods. The study included 29 patients with confirmed diagnosis of COPD with II and III degree of ventilation disorders according to the GOLD classification and an increase in FEV1 more than 200 ml (12 %) when carrying out a test with a bronchodilator. With the help of the patients’ spirograms retrospective analysis over the long period of observation an evaluation and comparison of the external respiration function parameters was performed: FVC, FEV1 and FEV6. Results. All patients were divided into 2 groups: group I included patients with a moderate degree of ventilation disorders severity by GOLD, group II – with severe impairment of external respiratory function. A reliable direct correlation between increments of FEV1 and FEV6, FVC and FEV6 (p < 0.05) was confirmed, which indicates a logical increase in FEV6 increment in parallel with the increase of FVC and FEV1 increments. When comparing the increase in FEV1 and FEV6 in group I it also was not noted significant differences. However, in group II FEV6 increment is two times higher than FEV1 increment with high probability (p < 0.05), which may be caused by the presence of more severe obstruction and longer expiration. Conclusions. It has been found a significant positive correlation of FEV6 with FEV1 and FVC and significant relationship between the FEV6 and FVC increments in both study groups, between the FEV6 and FEV1 increments in the group with grade III ventilation disorders by GOLD classification. Thus, FEV6 can be considered as a perspective indicator of the external respiration function evaluation, especially in patients with more severe course of the disease.